Study of Mechanical and Fatigue Behaviors of Nano Scaled B4C and Al2O3 Strengthened Aluminum Matrix Composites AMCs - Kako, Salim (Al-Nahrain Journal for Engineering Sciences, 2022)
The study here under describes the impact of adding a nano-scaled ceramic particles on the mechanical and fatigue behaviors of aluminum matrix composites AMCs containing 0.5 ,1.0 ,1.5, and 2 % wt. of nano-scaled B4C and Al2O3 particles were dispersed in molten aluminum by the stir-casting process. Vickers, tensile, and fatigue devices were utilized to evaluate the mechanical behavior of composites in the fabrication process. The results show that increasing the weight percentage of nano-ceramic particles increased the hardness, maximum tensile stress, and fatigue strengths of the base alloy. Furthermore, all of the above behaviors of AMCs reinforced with B4C particles are better than those of AMCs reinforced with Al2O3 particles.